2009
DOI: 10.1002/chem.200802229
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Redox Reactions for In‐Source Peptide Fragmentation

Abstract: Top stuff: The configuration of tetrafluoromethane–water is driven by dipole–dipole interactions rather than hydrogen bonds. The complex, which consists of a planar and a spherical moiety, is an asymmetric top in its equilibrium conformation, but its effective behavior is that of a symmetric top, owing to its high internal dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…6). Under the UV-laser irradiation on titania based SALDI-MS, it was reported that electrons are excited from the valence band to the conduction band of titania, producing oxidative holes to drive in-source oxidation reactions and reductive electrons to induce in-source reactions of analytes in SALDI-MS. 33), 48), 49) In this study, such UV-laser induced photocatalytic oxidation reactions were observed in the case of amorphous (or titania)-type titania with strong photocatalytic e#ects, but not for rutile-type titania with weak photocatalytic e#ects. As shown in Fig.…”
Section: Laser Threshold For Titania-based Saldi-msmentioning
confidence: 57%
“…6). Under the UV-laser irradiation on titania based SALDI-MS, it was reported that electrons are excited from the valence band to the conduction band of titania, producing oxidative holes to drive in-source oxidation reactions and reductive electrons to induce in-source reactions of analytes in SALDI-MS. 33), 48), 49) In this study, such UV-laser induced photocatalytic oxidation reactions were observed in the case of amorphous (or titania)-type titania with strong photocatalytic e#ects, but not for rutile-type titania with weak photocatalytic e#ects. As shown in Fig.…”
Section: Laser Threshold For Titania-based Saldi-msmentioning
confidence: 57%
“…With this affinity strategy, selective enrichment of low-abundance biomolecules can be achieved. More recently, semiconductor nanomaterials and quantum dots were used as photosensitive centers to induce in-source redox reactions to investigate the oxidation of biomolecules [276,277]. Several nanomaterials have also been used as matrices in MALDI-TOF/MS analysis due to their low heat conductivities and light-absorbing capabilities.…”
Section: Nanomaterials Enrichmentmentioning
confidence: 99%
“…During the investigation of photoinduced reductions, it was found that TiO 2 could also induce peptide regular fragmentation with the presence of glucose [31]. Specifically, glucose was oxidized by the holes, and the oxidized glucose could further oxidize the peptides and cleave the C a -C bond to generate a, x-fragments, as indicated in Figure 5.…”
Section: Nanomaterials To Induce In-source Reaction During the Maldi mentioning
confidence: 99%
“…TiO 2 semiconducting nanoparticles are widely used in the fi eld of phofield of phoof photocatalysis [29] and for the design of dye-sensitized solar cells. Under UV light irradiation, electrons in the valence band of TiO 2 can be excited into the conduction band, and both holes and electron can be trapped at the nanoparticle surface to form oxidative holes and reductive electrons able to react with surrounding molecules [30][31][32]. Using nano-TiO 2 to assist LDI, in-source redox reactions induced by these redox centers can be observed during the ionization processes [30][31][32].…”
Section: Nanomaterial-assisted Laser Desorption Ionizationmentioning
confidence: 99%
See 1 more Smart Citation